Development of Project Based e-Worksheet to Stimulate Scientific Creativity and Collaborative Skills - Titi Puspita Lupi; Kartini Herlina Herlina; Feriansyah Sesunan Sesunan; Doni Andra Andra (Universitas Lambung Mangkurat, 2021)
This study aimed to develop project-based e-worksheets using Fliphtml5 on light interference topic. This research used Design, Development, and Research (DDR) with the stages of analysis, design, development, and evaluation. To get a product that is feasible, this product must be valid and practical. Validity of the product’s design and construct was validated by 3 experts, indicating that the digital e-worksheet developed was categorized very valid with an average score of 3.44 and the practicality of the product in terms of the teacher’s and student’s responses with an average score of 85% was categorized very good. Based on the results of validity and practicality of product, it assumed that e-worksheet is feasible to stimulate students' science creativity and collaborative skills.